Geographic Information System Mapping of Kerosene Businesses In Jayapura - Andrian Sah; Rachman kurniawan; Jusmawati Jusmawati (Universitas Islam Kuantan Singingi, 2021)
The role of BBM is very important in people's lives. Fuel is a basic need for rural and urban communities, both as household needs and as business needs. The existence of kerosene in Jayapura is quite evenly distributed. From the results of survey conducted by the OFFICE OF INDUSTRY, COOPERATIVE TRADE AND SMEs that every year the use of LPG as fuel for cooking is still very low, while the use of kerosene from year to year is widely used by local community, it causes more kerosene bussiness but people have difficulty getting information about the location to get the kerosene, therefore we need a system that can help find the location, namely geographic information system that can provide information about fuel oil base points. This system is in symbols form for making the system using QGIS with the PIECES analysis method, the design using Unified Modeling Language (UML) method and the development method using waterfall method. This research produces a system that can be expected to make it easier for the public to know the distribution of kerosene in Jayapura